Fireproof and antiknock integrated coating paint for plugging transformer substation / converter station and preparation method of fireproof and antiknock integrated coating paint
By using the coating of an organic-inorganic two-component curing system in substations and converter stations, the problem of difficulty in achieving fire and explosion resistance in the prior art is solved, and the excellent fire resistance and explosion resistance of the coating is achieved, which reduces construction and maintenance cycles, and reduces material waste and economic losses.
Patent Information
- Application Number
- CN202510413328.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-03
AI Technical Summary
The prior art is difficult to achieve fire-proof and explosion-resistant performance in substations and converter stations at the same time, resulting in a long construction and maintenance cycle, and the separation design of fire-proof and explosion-resistant increases material waste and economic losses.
The organic-inorganic two-component curing system is adopted, including polyurea resin, graphene tube, nanotin antimony oxide, nanosilica, vermiculite powder and water glass. Through the combination of these components, the coating is achieved with excellent fire resistance and explosion-proof performance.
The fire resistance and explosion resistance performance of the substation and converter station sealing systems has been synchronized, which has reduced construction and maintenance cycles, reduced material waste and economic losses, and improved the fire resistance level and impact strength of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of coatings, and in particular to a fireproof and explosion-resistant integrated coating for plugging a transformer substation / converter station and a preparation method thereof. Background Art
[0002] The converter station is the core of the UHV DC project to achieve mutual conversion between AC and DC. Its operating reliability directly affects the safety of personnel and equipment and the stable operation of the power grid. The insulating oil in the converter transformer tank is more than 100 tons. Once the fault arc causes a fire or even an explosion, it will cause the valve hall fireproof sealing system to be damaged, and the fire will spread to the inside of the valve hall, which will cause immeasurable economic losses and social impact. The substation refers to the place where voltage and current are transformed, electric energy is received and distributed in the power system. The substation in the power plant is a step-up substation. Its function is to step up the electric energy generated by the generator and feed it into the high-voltage power grid. It is the hub of the entire power transmission and transformation system and plays an important role in connecting the upper and lower levels. Since substations often operate at high voltage and high current, the risk of fire is high and fire prevention measures are required.
[0003] After the Tianshan fire in 2018, the State Grid launched a fire protection improvement plan, dismantled the original converter station blocking system and installed explosion-proof doors with a dynamic load of no less than 80 kPa, which improved the safety margin of the converter transformer to a certain extent, but also greatly increased the construction period and the difficulty of maintenance. The separation design of fire protection and explosion resistance made the construction and replacement complicated, resulting in an extension of the maintenance cycle. Taking the ±800kV / 8GW UHV converter station as an example, the separation design of fire protection and explosion resistance will cause the maintenance cycle to be extended by 3-4 days. According to preliminary estimates, the economic loss of a ±800kV / 8GW UHV converter station that transmits power at half power is as high as 9.6 million yuan for one day of power outage.
[0004] At the same time, fire prevention measures taken in substations mainly include installing fire doors, which can block fire, provide escape routes, and act as smoke barriers when in use. The current substation fire doors focus on improving fire resistance, but have limited explosion resistance, and cannot simultaneously meet the requirements for integrated fire and explosion resistance for substation blocking.
[0005] Therefore, there is an urgent need to develop an integrated fireproof and explosion-proof coating for power plugging, which can not only improve the fire protection of substations / converter stations, but also avoid the waste of materials caused by dismantling the plugging, and at the same time can significantly reduce the economic losses caused by power outages. Summary of the invention
[0006] The present invention provides a fireproof and explosion-proof integrated coating for plugging of a substation / converter station and a preparation method thereof. In order to reduce the cost of converter station reconstruction and improve the fire resistance and explosion-proof functions of the protective door of the plugging system of the substation / converter station, an organic-inorganic two-component curing system is adopted to achieve excellent fire resistance and explosion-proof capabilities of the coating. The fire resistance and explosion-proof designs are implemented simultaneously to improve construction efficiency.
[0007] In order to solve the above technical problems, one of the purposes of the present invention is to provide a fireproof and explosion-proof integrated coating for plugging a substation / converter station, comprising the following components in parts by weight: Polyurea resin: 5-8 parts; Graphene tube: 0.5-3 parts; Nano antimony tin oxide: 0.5-5 parts; Nano silicon dioxide: 20-30 parts; Vermiculite powder: 30-50 parts; Water glass: 20-40 parts.
[0008] The inventor of the present application has found through multiple experiments and studies that by adding polyurea resin as an organic component, adding water glass as an inorganic curing agent and cross-linking agent, and nano-silicon dioxide as an inorganic thickener, the organic-inorganic two-component curing system solves the current problem that the organic coating is not fire-resistant and the inorganic coating is easy to crack and is not explosion-proof. At the same time, nano-level silicon dioxide reduces the heat solid conduction of the material, reduces the thermal conductivity, and improves the fire resistance level. High-refractive nano-tin antimony oxide can effectively block infrared radiation and improve the fire resistance of the coating. The anti-transmission mechanism of nano-tin antimony oxide can promote the uniformity of particles in the coating and improve the impact strength of the coating. In addition, vermiculite powder is a structure containing vermiculite flakes and cavity particles. The contact area between the solids is small, and the solid heat conduction is relatively weak, that is, it can store heat and reduce the thermal conductivity of the material. The vermiculite powder is strengthened by graphene tubes and promoted to absorb impact energy. When it is used for fire and explosion prevention of substations / converter stations, it can have both fire resistance and impact resistance, and has excellent explosion-proof effect.
[0009] As a preferred embodiment, the polyurea resin is a water-based asparagine polyurea resin.
[0010] As a preferred solution, the viscosity of the polyurea resin is 400-1500 mPas. The polyurea resin can be used as a dispersant for inorganic components and as a carrier for nanomaterials to improve bonding strength, avoid cracking of the coating, and improve impact strength.
[0011] As a preferred embodiment, the viscosity of the polyurea resin is within the range of any one or any two of 400 mPas, 500 mPas, 600 mPas, 700 mPas, 800 mPas, 900 mPas, 1000 mPas, 1100 mPas, 1200 mPas, 1300 mPas, 1400 mPas, and 1500 mPas.
[0012] As a preferred solution, the viscosity of the polyurea resin is 1000-1300 mPas. The viscosity of the polyurea resin within this range can meet the bonding strength of the organic-inorganic curing system and maximize the impact resistance and crack resistance of the coating. At the same time, less organic components need to be added, which can avoid the organic components affecting the fire resistance level of the coating, thereby achieving a balance.
[0013] As a preferred embodiment, the particle size of the nano-silicon dioxide is 10-100 nm, and the purity is ≥93%.
[0014] Nano-silica is mainly used as an inorganic thickener. Compared with organic thickeners, it can greatly improve the fire retardant performance of the coating. Nano-silica is a nano-powder, which can reduce the heat solid conduction of the material and reduce the thermal conductivity. Nano-silica accounts for a high proportion in the coating. Controlling the particle size of nano-silica within the above range can avoid large particles and high thermal conductivity, and avoid small particles agglomerating and increasing thermal conductivity.
[0015] As a preferred embodiment, the particle size of the nano-silicon dioxide is any one or any two of 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 75nm, 80nm, 85nm, and 90nm.
[0016] As a preferred solution, the particle size of the nano-silicon dioxide is 40-80 nm, and the preferred purity is ≥95.5%.
[0017] As a preferred solution, the particle size of the nano antimony tin oxide is 20-80 nm, and the purity is ≥99%. The nano antimony tin oxide has a high transmittance in the visible light region and a high blocking rate in the infrared light region, which increases the transparency of the coating and the infrared blocking effect at high temperatures, thereby improving the aesthetics and fire resistance of the coating.
[0018] As a preferred embodiment, the particle size of the nano antimony tin oxide is any one or any two of 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, and 80nm.
[0019] As a preferred solution, the particle size of the nano antimony tin oxide is 50-70 nm, and the preferred purity is ≥99.5%.
[0020] As a preferred embodiment, the specific surface area of the graphene tube is 1000-1500m 2 / g, the structure of graphene tubes is usually composed of a two-dimensional honeycomb crystal structure composed of single or multi-layer graphene, which mainly plays a role in strengthening the strength of vermiculite powder and absorbing impact energy. Graphene tubes are micro-nano materials. If the specific surface area is too high, there will be a strong adsorption effect between particles, which is easy to agglomerate and affect the mechanical strength of the coating; if the specific surface area is too small, the contact area between particles and other materials will increase, which will increase heat transfer and affect the fire resistance of the material. If the specific surface area is controlled within the above range, the dispersion effect of graphene tubes can be improved, while reducing the thermal conductivity and improving the fire resistance level.
[0021] As a preferred embodiment, the specific surface area of the graphene tube is 1000m 2 / g, 1050m 2 / g、1100m 2 / g, 1150m 2 / g、1200m 2 / g, 1250m 2 / g、1300m 2 / g, 1350m 2 / g、1400m 2 / g, 1450m 2 / g、1500m 2 / g or both.
[0022] As a preferred embodiment, the specific surface area of the graphene tube is 1100-1300 m 2 / g.
[0023] As a preferred embodiment, the vermiculite powder is obtained by thermally expanding and grinding vermiculite flakes at 400-600°C.
[0024] As a preferred embodiment, the vermiculite powder has a particle size of 0.1-1 mm and a loose bulk density of 200-250 kg / m 3 .
[0025] As a preferred embodiment, the particle size of the vermiculite powder is within the range of any one or any two of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, and 1 mm.
[0026] As a preferred embodiment, the vermiculite powder has a particle size of 0.4-0.6 mm and a loose bulk density of 220-240 kg / m3 .
[0027] As a preferred embodiment, the mass ratio of the nano-silicon dioxide, vermiculite powder and water glass is 30: (35-75): (25-30).
[0028] In the present application, water glass is used as an inorganic curing agent and cross-linking agent, which plays an important role in the stability of the entire component system. Nano-silicon dioxide is used to provide thickening and reduce thermal conductivity, and vermiculite powder provides strength and reduces thermal conductivity. By controlling the proportion range of the three, the flame retardant and fire resistant functions of the coating can be effectively improved, while the strength of the coating can be improved. The structure is tightly bonded and excellent in explosion protection.
[0029] As a preferred embodiment, the mass ratio of the nano-silicon dioxide, vermiculite powder and water glass is 5:9:5.
[0030] As a preferred solution, the modulus of the water glass is 1.5-3.5.
[0031] As a preferred embodiment, the modulus of the water glass is any one of or any two of 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, 3.1, 3.2, 3.3, 3.4, and 3.5.
[0032] As a preferred solution, the modulus of the water glass is 3.2-3.4.
[0033] As a preferred embodiment, the coating material comprises the following components in parts by weight: Polyurea resin: 5-7 parts; Graphene tube: 1-3 parts; Nano antimony tin oxide: 1-3 parts; Inorganic thickener: 22-28 parts; Vermiculite powder: 42-48 parts; Water glass: 22-28 parts.
[0034] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing a fireproof and explosion-proof integrated coating for plugging a substation / converter station, comprising the following steps: S1, stirring and mixing the graphene tube and nano-antimony tin oxide to obtain a mixed filler; S2, uniformly mixing the mixed filler and the polyurea resin, and freeze-drying the mixture after the reaction to obtain a polyurea resin modified aerogel; S3, mixing vermiculite powder and nano-silicon dioxide evenly, then dissolving them into water glass, and stirring to form a stable suspension; S4, stirring and mixing the aerogel and the suspension to obtain a coating.
[0035] As a preferred solution, in S1, the stirring rate is 300-1000 rpm, and the stirring time is 2-4 min.
[0036] As a preferred embodiment, in S2, the reaction temperature is 40-100°C and the reaction time is 6-18 h.
[0037] As a preferred embodiment, in S4, the stirring rate is 200-500 rpm, and the stirring time is 12-48 h.
[0038] In order to solve the above technical problems, the third object of the present invention is to provide a fireproof and explosion-proof door for sealing a substation / converter station, comprising a plate and an integrated fireproof and explosion-proof coating on the surface of the plate, wherein the integrated fireproof and explosion-proof coating is prepared using the above-mentioned integrated fireproof and explosion-proof coating for sealing a substation / converter station.
[0039] As a preferred solution, the thickness of the fireproof and explosion-resistant integrated coating is 15-20 mm, and the thickness of the plate is 20-30 mm.
[0040] Compared with the prior art, the present invention has the following beneficial effects: 1. The present application simultaneously adds polyurea resin as an organic component, water glass as an inorganic curing agent and cross-linking agent, and nano-silica as an inorganic thickener. The organic-inorganic two-component curing system solves the problem that the current organic coating is not fire-resistant and the inorganic coating is easy to crack and is not explosion-proof, while improving the fire resistance and impact resistance. At the same time, nano-level silica reduces the heat solid conduction of the material and reduces the thermal conductivity. The added vermiculite powder contains vermiculite flakes and cavity particle structures, and the solid heat conduction is relatively weak, which further improves the fire resistance level.
[0041] 2. Adding highly refractive nano antimony tin oxide to the coating of the present application can effectively block infrared radiation and improve the fireproof performance of the coating. The anti-reflection mechanism of nano antimony tin oxide can promote the uniformity of particles in the coating and improve the impact strength of the coating.
[0042] 3. The vermiculite powder added in this application has a hollow particle structure, which has the function of absorbing energy and reducing thermal conductivity. The graphene tube is used to enhance the strength of the vermiculite powder and promote the impact energy absorption, which can improve the fire resistance and impact resistance.
[0043] 4. The preparation method of the present invention is simple and quick to operate. The composite protective coating material prepared thereby is used for the plugging system of a substation / converter station, which can effectively solve the problems of difficulty and long cycle in its construction and maintenance. DETAILED DESCRIPTION
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0047] As used herein: "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0048] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0049] In these examples, parts and percentages are by mass unless otherwise indicated.
[0050] "Parts by mass" refers to the basic unit of measurement that indicates the proportional relationship of the masses of multiple components. 1 part can represent any unit mass. It should not be misunderstood that, unlike the number of parts by mass, the sum of the parts by mass of all components is not limited to 100 parts.
[0051] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0052] In the description of the present invention, it is necessary to understand that the terms "up", "down", "left", "right", "top", "bottom", etc., indicating directions or positional relationships, are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.
[0053] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with the examples, but they should not be understood as limiting the scope of protection of the present invention. The following Table 1 is the source information of the raw materials used in the examples and comparative examples of the present application. Unless otherwise specified, the raw materials used can be obtained from the market, and the same raw materials are used in parallel experiments.
[0054] Table 1 - Source information of raw materials used in the examples and comparative examples of this application Example 1 A fireproof and explosion-proof integrated coating for plugging a substation / converter station, comprising 2 kg of graphene tubes, 6 kg of water-based asparagus polyurea resin, 2 kg of nano antimony tin oxide, 25 kg of nano silicon dioxide, 45 kg of vermiculite flakes, and 25 kg of water glass, wherein the specific surface area of the graphene tubes is 1250 m 2 / g, the particle size of nano silicon dioxide is 75 nm, the purity is 97%, the viscosity of water-based aspartame polyurea is 1100mPas, the particle size of nano antimony tin oxide is 60 nm, the purity is ≥99%, and the modulus of water glass is 3.3. The preparation method comprises the following steps: S1. Mix the graphene tube and nano-antimony tin oxide evenly, and stir them for 3 min using a high-speed stirrer at a stirring rate of 500 rpm to obtain a mixed filler; S2, uniformly mixing the mixed filler with the aqueous asparagine polyurea resin solution, reacting at 60°C for 12 h, and freeze-drying to obtain a polyurea resin modified aerogel; S3, the vermiculite flakes were subjected to thermal expansion at 500 °C and ground to obtain vermiculite powder with a particle size of 0.5 mm and a loose bulk density of 220 kg / m 3, mix evenly with nano-silicon dioxide, dissolve the powder into water glass, and stir to form a stable suspension; S4. Place the aerogel and the suspension in a magnetic stirrer and mix them. Stir them at a rate of 300 r / min for 24 h to fully dissolve them and obtain a coating.
[0055] Example 2 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment, and process parameters used in each step of the preparation method are the same as those in Example 1. The difference is that the coating comprises 1 kg of graphene tubes, 5 kg of water-based asparagine polyurea resin, 1 kg of nano-antimony tin oxide, 20 kg of nano-silicon dioxide, 30 kg of vermiculite flakes, and 20 kg of water glass, wherein the specific surface area of the graphene tubes is 1250 m 2 / g, the particle size of nano-silica is 75 nm, the purity is ≥95.5%, the viscosity of water-based aspartame polyurea is 1100mPas, the particle size of nano-antimony tin oxide is 60 nm, the purity is ≥99%, and the modulus of water glass is 3.3.
[0056] Example 3 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment, and process parameters used in each step of the preparation method are the same as those in Example 1. The difference is that the coating comprises 3 kg of graphene tubes, 8 kg of water-based asparagine polyurea resin, 4 kg of nano-antimony tin oxide, 30 kg of nano-silicon dioxide, 50 kg of vermiculite flakes, and 40 kg of water glass, wherein the specific surface area of the graphene tube is 1250 m 2 / g, the particle size of nano-silica is 75 nm, the purity is ≥95.5%, the viscosity of water-based aspartame polyurea is 1100mPas, the particle size of nano-antimony tin oxide is 60 nm, the purity is ≥99%, and the modulus of water glass is 3.3.
[0057] Example 4 A fireproof and explosion-proof integrated coating for plugging a substation / converter station, wherein the reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the specific surface area of the graphene tube is 1500m 2 / g.
[0058] Example 5 A fireproof and explosion-proof integrated coating for plugging a transformer substation / converter station, wherein the reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the particle size of the nano-silicon dioxide is 100 nm.
[0059] Example 6 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1. The difference is that the content of nano-silicon dioxide in the coating is 30 kg, the content of vermiculite flakes is 35 kg, and the content of water glass is 25 kg.
[0060] Example 7 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1. The difference is that the content of nano-silicon dioxide in the coating is 20 kg, the content of vermiculite flakes is 50 kg, and the content of water glass is 20 kg.
[0061] Comparative Example 1 A fireproof and explosion-proof integrated coating for plugging a substation / converter station, wherein the reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the amount of graphene tube added is 0.
[0062] Comparative Example 2 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the amount of nano-tin antimony oxide added to the coating is 0.
[0063] Comparative Example 3 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1. The difference is that the content of nano-silicon dioxide in the coating is 30 kg, the content of vermiculite flakes is 25 kg, and the content of water glass is 35 kg.
[0064] Comparative Example 4 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1. The difference is that the content of nano-silicon dioxide in the coating is 40 kg, the content of vermiculite flakes is 25 kg, and the content of water glass is 25 kg.
[0065] Comparative Example 5 A fireproof and explosion-proof integrated coating for plugging a transformer substation / converter station, wherein the reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the vermiculite powder in S3 is replaced by mica with a particle size of 0.5 mm in an equal amount.
[0066] Comparative Example 6 A fireproof and explosion-proof integrated coating for plugging a transformer substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the vermiculite powder in S3 is replaced by an equal amount of nano-silicon dioxide.
[0067] Comparative Example 7 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1. The difference is that the water-based aspartame polyurea resin in the coating is replaced by an equal amount of acrylic resin.
[0068] Comparative Example 8 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the amount of water-based aspartame polyurea resin added to the coating is 0.
[0069] Comparative Example 9 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that the graphene tube is replaced by an equal amount of nano-tin oxide antimony.
[0070] Comparative Example 10 A fireproof and explosion-proof integrated coating for plugging a substation / converter station. The reagents, equipment and process parameters used in each step of the preparation method are the same as those in Example 1, except that nano antimony tin oxide is replaced by an equal amount of graphene tubes.
[0071] Performance testing 1. Fireproof performance: The coating prepared in the above embodiments and comparative examples was applied on the surface of a 25 mm plate by a brush coating method, the coating thickness was controlled to be 15 mm, and the plate was placed in the air for 48 hours to ensure complete drying. At the same time, plates coated with commercially available samples 1 and 2 of the same thickness were used as a control group. According to the method described in GB 23864-2023 "Fireproof Sealing Materials", the fire resistance limit of the plate was tested. The test results are shown in Table 2 below.
[0072] 2. Explosion resistance: According to the standard Q / IEM 3003.39-2011 "Test method for explosion resistance and explosion relief performance of doors and windows", the impact strength of the plates coated with the coatings of the embodiments and comparative examples was tested. The test results are shown in Table 2 below.
[0073] Table 2 - Performance test results of the plates containing the coatings of the present application examples and comparative examples As shown in Table 2, the addition of graphene tubes with a two-dimensional honeycomb crystal structure in Example 1 of the present application can enhance the strength of vermiculite powder, while also improving the impact energy absorption effect, improving the impact strength of the coating, and having excellent explosion-proof effect. However, in Comparative Example 1, no graphene tube component was added, resulting in a 33% decrease in the impact strength of the coating, and poor explosion-proof ability. The graphene tubes of Comparative Example 9 were replaced by nano-antimony tin oxide, resulting in a decrease in the impact resistance of the coating and insufficient explosion-proof ability.
[0074] As shown in Table 2, nano antimony tin oxide is added to Example 1 of the present application. Nano antimony tin oxide has a high transmittance in the visible light region and a high blocking rate in the infrared light region, which increases the transparency of the coating and the infrared blocking effect at high temperatures, thereby improving the fire resistance of the coating. However, the coating of Comparative Example 2 does not contain nano antimony tin oxide, which results in a decrease in the fire resistance limit time of the coating and a decrease in the fireproof ability. The nano antimony tin oxide of Comparative Example 10 is replaced by a graphene tube, and the coating cannot effectively block infrared light under high temperature conditions, and the fire resistance performance is significantly reduced.
[0075] As shown in Table 2, in Examples 1, 6-7 of the present application, the ratio of nano-silicon dioxide, vermiculite powder and water glass in the suspension is controlled to be 30: (35-75): (25-30), water glass is used to provide curing and cross-linking effects, nano-silicon dioxide reduces the thermal conductivity and provides a thickening effect to ensure uniform system particles, vermiculite powder further reduces the thermal conductivity, and has energy absorption and strength enhancement effects. By controlling the ratio of the three within the above range, the fire resistance and impact resistance can be balanced; while in Comparative Example 3, the proportion of vermiculite flakes is too low, resulting in a decrease in the fire resistance level of the coating, and in Comparative Example 4, the proportion of nano-silicon dioxide is too high and the proportion of vermiculite powder is too low, resulting in a decrease in the fire resistance and impact strength of the coating.
[0076] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A fireproof and explosion-proof integrated coating for plugging a substation / converter station, characterized in that: It comprises the following components in parts by weight: Polyurea resin: 5-8 parts; Graphene tube: 0.5-3 parts; Nano antimony tin oxide: 0.5-5 parts; Nano silicon dioxide: 20-30 parts; Vermiculite powder: 30-50 parts; Water glass: 20-40 parts.
2. The fireproof and explosion-proof integrated coating material for plugging a substation / converter station according to claim 1, characterized in that: The polyurea resin is a water-based aspartame polyurea resin; And / or, the viscosity of the polyurea resin is 400-1500 mPas.
3. The fireproof and explosion-proof integrated coating material for plugging a substation / converter station according to claim 1, characterized in that: The particle size of the nano antimony tin oxide is 20-80 nm, and the purity is ≥99%; And / or, the nano-silicon dioxide has a particle size of 10-100 nm and a purity of ≥93%.
4. The fireproof and explosion-proof integrated coating material for plugging a substation / converter station according to claim 1, characterized in that: The specific surface area of the graphene tube is 1000-1500 m 2 / g.
5. The fireproof and explosion-proof integrated coating material for plugging a substation / converter station according to claim 1, characterized in that: The vermiculite powder is obtained by thermal expansion of vermiculite flakes at 400-600°C and grinding; And / or, the vermiculite powder has a particle size of 0.1-1 mm and a loose bulk density of 200-250 kg / m 3 .
6. The fireproof and explosion-proof integrated coating material for plugging a substation / converter station according to claim 1, characterized in that: The mass ratio of the nano silicon dioxide, vermiculite powder and water glass is 30: (35-75): (25-30).
7. The fireproof and explosion-proof integrated coating material for plugging a substation / converter station according to claim 1, characterized in that: The modulus of the water glass is 1.5-3.
5.
8. A method for preparing the fireproof and explosion-proof integrated coating for plugging a substation / converter station according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, stirring and mixing the graphene tube and nano-antimony tin oxide to obtain a mixed filler; S2, uniformly mixing the mixed filler and the polyurea resin, and freeze-drying the mixture after the reaction to obtain a polyurea resin modified aerogel; S3, mixing vermiculite powder and nano-silicon dioxide evenly, then dissolving them into water glass, and stirring to form a stable suspension; S4, stirring and mixing the aerogel and the suspension to obtain a coating.
9. The method for preparing the fireproof and explosion-proof integrated coating for plugging a substation / converter station according to claim 8, characterized in that: In S1, the stirring rate was 300-1000 rpm and the stirring time was 2-4 min; and / or, in S2, the reaction temperature is 40-100°C and the reaction time is 6-18 h; and / or, in S4, the stirring rate is 200-500 rpm and the stirring time is 12-48 h.
10. A fireproof and explosion-proof door for plugging a transformer substation / converter station, characterized in that: It comprises a plate and a fireproof and explosion-proof integrated coating located on the surface of the plate, wherein the fireproof and explosion-proof integrated coating is prepared by using the fireproof and explosion-proof integrated coating paint for plugging a substation / converter station as described in any one of claims 1-7.
Citation Information
Patent Citations
Hydrocarbon resistance fire-proof and explosion-proof coating
CN105694648A
Improved fire-retardant coating
CN107163778A
Method for preparing water-based fireproof anticorrosive paint by filling aluminum tripolyphosphate-expanded vermiculite-water glass
CN110643247A
Indoor conductive heating coating
CN111560195A
Fireproof and explosion-proof insulating plugging material
CN112552669A